Proposta de atividades nas escolas: parceria Unesp, Cooperlix e Secretaria Municipal do Meio Ambiente de Presidente Prudente - Pacetti, Ana Maria [UNESP]; Okimoto, Fernando Sérgio [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This paper presents an activity performed on a school Presidente Prudente as part of a municipal agenda of environmental education on the management of recyclable waste in the municipality of Presidente Prudente. The activity was attended by the author, from conception until the realization and was planned as one of the activities under the University Extension project entitled "Environmental education through the Social Integration Centers and Environmental Sustainability - CISSAs" It is clear that these interactive activities are powerful tools in raising awareness of children and increase the cognition of the treated environmental issues.

Este trabalho apresenta a atividade realizada em uma escola de Presidente Prudente como parte de uma agenda municipal de Educação Ambiental sobre a gestão dos resíduos recicláveis no município de Presidente Prudente. A atividade teve a participação da autora, desde a concepção até a realização e foi planejada como mais uma das atividades previstas no projeto de Extensão Universitária “A Educação Ambiental através dos Centros de Integração Social e Sustentabilidade Ambiental - CISSAs” Percebe-se que essas atividades interativas são ferramentas poderosas na conscientização das crianças e aumentam a cognição das questões ambientais tratadas.
Keywords: Environmental education; Recyclable waste; Educação ambiental; Resíduos recicláveis